Pengembangan Media Pembelajaran Monopoli untuk Meningkatkan Keterampilan 7c di SILN Kota Kinabalu - Januar, Exsaris; Gistuati, Nurhizrah; Fitria, Yanti; Sahyuddin, Sahyuddin (Jurnal Didaktika Pendidikan Dasar, 2025)
One of the learning problems that occurs at the elementary school level is the lack of student activity in learning. Students also do not practice the 21st century skills written in the 7Cs, namely computational thinking, Compassion, Citizenship, Critical Thinking, Creativity, Collaboration, and Communication. Appropriate learning media are needed to train students' 21st century skills in learning. This type of research is development research (research and development) with 4D development steps. The aim of this research is to produce valid, practical and effective learning media to train the 7C skills of elementary school level students in the science and science subject Phase C Class 5. The place and object of this research is the Indonesian Overseas School in Kota Kinabalu, Sabah Malaysia with students Class V consists of 30 students registered at Dapodik for the 2023/2024 academic year. The conclusion of this research is that the IKN Monopoly learning media is very valid, effective and practical in learning Natural and Social Sciences.